The price of gender equality: Member States and governance in the European Union - van der Vleuten, Anna (Aldershot, 2007)
"This book presents a thorough and well-documented theoretically guided empirical analysis of gender equality policies in the European Union (EU). Inspite of a wealth of research, many questions remain unanswered. To deal with these, a theoretical framework is required which is able to explain the changing fortunes of women's activism, the changing attitudes of European institutions and the behaviour of member states in a multi-level setting."